Site characterization of a tropical soil by in situ tests - Rocha, Breno Padovezi (2018)
This paper compiles site characterization data of an unsaturated tropical soil profile in an experimental research site in Bauru, São Paulo State, Brazil. Several in situ campaigns comprised geophysical borehole tests (cross-hole, down-hole and up-hole together with the SPT), as well as mechanical tests (SPT, CPT and SDMT) have been performed. According to the MCT Classification System for tropical soils, the first 13 m depth is a colluvium with lateritic soil behavior (LA’) over the residual soil with non-lateritic behavior (NA’). The ratio between seismic (Go) and mechanical (qn, N60, ED, KD and MDMT) parameters was useful to identify the presence of microstructure and to confirm unusual soil behavior for this tropical soil site. CPT and SDMT were efficient for detailed stratigraphic logging, however, the estimative of geotechnical parameters cannot be solely been done base on just conventional correlations defined for sedimentary soil.